Strategic risk dominance in collective systems design. (2019) - Grogan, Paul T.; Valencia-Romero, Ambrosio
Abstract : Engineered system architectures leveraging collaboration among multiple actors across organizational boundaries are envisioned to be more flexible, robust, or efficient than independent alternatives but also carry significant downside risks from new interdependencies added between constituents. This paper transitions the concept of risk dominance from equilibrium selection in game theory to engineering design as a strategic measure of collective stability for system of systems. A proposed method characterizes system design as a bi-level problem with two or more asymmetric decision-makers. A measure of risk dominance assesses strategic dynamics with respect to the stability of joint or collaborative architectures relative to independent alternatives using a novel linearization technique to approximate linear incentives among actors. An illustrative example case for an asymmetric three-player design scenario shows how strategic risk dominance can identify and mitigate architectures with unstable risk-reward dynamics.